2012
DOI: 10.1111/ppl.12009
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana organellar DNA polymerase IB mutants exhibit reduced mtDNA levels with a decrease in mitochondrial area density

Abstract: Plant organelle genomes are complex and the mechanisms for their replication and maintenance remain unclear. Arabidopsis thaliana has two DNA polymerase genes, DNA polymerase IA (polIA) and polIB, that are dual targeted to mitochondria and chloroplasts and are differentially expressed in primary plant tissues. PolIB gene expression occurs at higher levels in tissues not primary for photosynthesis. Arabidopsis T-DNA polIB mutants have a 30% reduction in relative mitochondrial DNA (mtDNA) levels, but also exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 46 publications
6
37
1
Order By: Relevance
“…Interestingly, a similar high-light tolerance was reported in msh1, but the exact cause of this adaptation remains elusive, as both chloroplast and mitochondria exhibit genomic instability in this mutant (Xu et al, 2011). Similarly to Msh1, PolIB is known to act in both organelles (Parent et al, 2011;Cupp and Nielsen, 2012), and thus it is possible that alterations in DNA metabolism from both chloroplast and mitochondria contribute to the nuclear genetic reprogramming observed in why1why3polIb-1. However, the synergistic increase in ptDNA rearrangements observed when plastid-localized Whirly proteins and PolIB are affected suggests that chloroplast defects are the main factor at the origin of changes in the nuclear gene expression.…”
Section: Discussion Plastid Genome Instability Leads To Impairment Ofmentioning
confidence: 58%
See 1 more Smart Citation
“…Interestingly, a similar high-light tolerance was reported in msh1, but the exact cause of this adaptation remains elusive, as both chloroplast and mitochondria exhibit genomic instability in this mutant (Xu et al, 2011). Similarly to Msh1, PolIB is known to act in both organelles (Parent et al, 2011;Cupp and Nielsen, 2012), and thus it is possible that alterations in DNA metabolism from both chloroplast and mitochondria contribute to the nuclear genetic reprogramming observed in why1why3polIb-1. However, the synergistic increase in ptDNA rearrangements observed when plastid-localized Whirly proteins and PolIB are affected suggests that chloroplast defects are the main factor at the origin of changes in the nuclear gene expression.…”
Section: Discussion Plastid Genome Instability Leads To Impairment Ofmentioning
confidence: 58%
“…In Arabidopsis (Arabidopsis thaliana), PolIA and PolIB, two type-I DNA polymerases, are proposed to perform chloroplast DNA replication (Mori et al, 2005;Parent et al, 2011). The mutation of either of the genes encoding these proteins is enough to cause replication stress, and PolIB has been demonstrated to have additional roles in DNA repair (Parent et al, 2011) and mitochondrial homeostasis (Cupp and Nielsen, 2012). In addition to PolIB, plant organelles possess Whirly proteins that act as safeguards of plastid genome stability by binding and stabilizing single-stranded DNA, thereby limiting the occurrence of illegitimate recombination (Maréchal et al, 2009;Cappadocia et al, 2010).…”
mentioning
confidence: 99%
“…The identified DNA polymerase was first isolated from plastids of rice, and its localization was confirmed by immunoblot analysis of isolated plastids (Kimura et al, 2002). Subsequent studies using GFP-fusion proteins and/or immunoblotting demonstrated that the polymerases, which were named PolI-like, PolI or Polγ, are localized to both plastids and mitochondria in Arabidopsis thaliana and tobacco (Christensen et al, 2005; Mori et al, 2005; Ono et al, 2007; Parent et al, 2011; Cupp and Nielsen, 2013). We also identified this type of DNA polymerase in algae and ciliates (Moriyama et al, 2008, 2011, 2014).…”
Section: Replication Dna Polymerase Popmentioning
confidence: 99%
“…The spatial expression patterns of POPs were analyzed in A. thaliana and rice by in situ hybridization, which revealed that POP genes are strongly expressed in the apical meristems of roots and shoots, leading to high POP protein levels in these tissues (Kimura et al, 2002; Mori et al, 2005). In A. thaliana , the expression of two POPs, AtPOP1 (At1g80840) and AtPOP2 (At3g20540), were compared by quantitative RT-PCR (Cupp and Nielsen, 2013). The analysis demonstrated that AtPOP1 is mainly expressed in rosette leaves, whereas AtPOP2 is predominantly found in the meristems of roots and shoots.…”
Section: Replication Dna Polymerase Popmentioning
confidence: 99%
See 1 more Smart Citation